Human organotypic retinal cultures (HORCs) as a chronic experimental model for investigation of retinal ganglion cell degeneration. (February 2016) - Osborne, Andrew; Hopes, Marina; Wright, Phillip; Broadway, David C.; Sanderson, Julie
Abstract: There is a growing need for models of human diseases that utilise native, donated human tissue in order to model disease processes and develop novel therapeutic strategies. In this paper we assessed the suitability of adult human retinal explants as a potential model of chronic retinal ganglion cell (RGC) degeneration. Our results confirmed that RGC markers commonly used in rodent studies (NeuN, βIII Tubulin and Thy-1) were appropriate for labelling human RGCs and followed the expected differential expression patterns across, as well as throughout, the macular and para-macular regions of the retina. Furthermore, we showed that neither donor age nor post-mortem time (within 24 h) significantly affected the initial expression levels of RGC markers. In addition, the feasibility of using human post mortem donor tissue as a long-term model of RGC degeneration was determined with RGC protein being detectable up to 4 weeks in culture with an associated decline in RGC mRNA and significant, progressive, apoptotic labelling of NeuN + cells. Differences in RGC apoptosis might have been influenced by medium compositions indicating that media constituents could play a role in supporting axotomised RGCs. We propose that using ex vivo human explants may prove to be a useful model for testing the effectiveness of neuroprotective strategies. Highlights: Human retina can be used to measure RGC degeneration over 4 weeks in culture. There are strong similarities between post mortem tissue and living donor retina. NeuN, βIII tubulin and Thy-1 are reliable markers of human RGCs. Starting RGC expression is not affected by donor age or post mortem time. Donor human retina could be a valuable resource as a model of chronic glaucoma.